Ultrafast electronic relaxation pathways of the molecular photoswitch quadricyclane - Borne, Kurtis D.; Cooper, Joseph C.; Ashfold, Michael N. R.; Bachmann, Julien; Bhattacharyya, Surjendu; Boll, Rebecca; Bonanomi, Matteo; Bosch, Michael; Callegari, Carlo; Centurion, Martin; Coreno, Marcello; Curchod, Basile F. E.; et al. (Nature Chemistry, 2024)
The light-induced ultrafast switching between molecular isomers norbornadiene and quadricyclane can reversibly store and release a substantial amount of chemical energy. Prior work observed signatures of ultrafast molecular dynamics in both isomers upon ultraviolet excitation but could not follow the electronic relaxation all the way back to the ground state experimentally. Here we study the electronic relaxation of quadricyclane after exciting in the ultraviolet (201 nanometres) using time-resolved gas-phase extreme ultraviolet photoelectron spectroscopy combined with non-adiabatic molecular dynamics simulations. We identify two competing pathways by which electronically excited quadricyclane molecules relax to the electronic ground state. The fast pathway (<100 femtoseconds) is distinguished by effective coupling to valence electronic states, while the slow pathway involves initial motions across Rydberg states and takes several hundred femtoseconds. Both pathways facilitate interconversion between the two isomers, albeit on different timescales, and we predict that the branching ratio of norbornadiene/quadricyclane products immediately after returning to the electronic ground state is approximately 3:2.<br
Keywords: Chemical physics; Photochemistry